Adaptasi Masyarakat terhadap Perubahan Penutup Lahan di Kecamatan Kelapa Kampit, Belitung Timur - Rahmawati, Emma; Purwanto, Anang Dwi (Faculty of Social Science, Universitas Negeri Semarang, 2019)
Land cover changes occur in Indonesia where one of them is in Kelapa Kampit, East Belitung Regency. This area is very famous for large-scale tin mining activities carried out by tin companies. Along with the policy on mining activities that must care about the surrounding environment and reclamation and revegetation activities carried out in post-mining land, the massive tin mining activities in the region are decreasing. This study aims to analyze changes in land cover and find out the adaptation of the community carried out due to changes in land cover and to know the factors that influence the adaptation strategy. This study uses the mixed methods approach. The data used include in the form of Landsat TM satellite imagery acquisition in 1995 and Landsat 8 acquisition in 2015 and interview data. The method of separating land cover objects using the technique of not guided digital classification. After the reclassification process has been carried out, 8 (eight) classes of land cover are produced. The results of the study show (1) there are contradictory conditions between mining land and forests with oil palm plantations. The condition of the mining area and forests from 1994 - 2015 decreased, while the area of oil palm plantations increased significantly. (2) The community adapts to varying sources of income, changes mining areas and relies on assistance from various parties (3) The factors that determine community adaptation are education, knowledge, environmental conditions, people's understanding of job other than mining, sources of income and assistance provided to the community.